If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 11 = 124 + -9x Reorder the terms: 11 + 6x = 124 + -9x Solving 11 + 6x = 124 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 11 + 6x + 9x = 124 + -9x + 9x Combine like terms: 6x + 9x = 15x 11 + 15x = 124 + -9x + 9x Combine like terms: -9x + 9x = 0 11 + 15x = 124 + 0 11 + 15x = 124 Add '-11' to each side of the equation. 11 + -11 + 15x = 124 + -11 Combine like terms: 11 + -11 = 0 0 + 15x = 124 + -11 15x = 124 + -11 Combine like terms: 124 + -11 = 113 15x = 113 Divide each side by '15'. x = 7.533333333 Simplifying x = 7.533333333
| 1/4x+1/2=4 | | (7x+4w+4)(5x-3w)=0 | | 1+2x/7+3-x/3=46/21 | | 7(x+8)=5x+44 | | -3(8p+2)-2(3-23p)=3(6+7p) | | (1-q)(1-q)=0 | | (1+q)(1+q)=0 | | 6=a/7 | | (29b-1)-7(4b+1)=-5 | | -f+5w+8= | | 5u-8/7=47/9 | | 49-9u-4/2 | | 5u-8/7=49-9u-4/2 | | x+3/5=40 | | 7/5x-4=-2/3x+6/5 | | -7/5w+1/3=-2/5w-2 | | -5/2u-7/2=4u+3/5 | | 8=-64 | | 4(2x-1)-(4x-3)=10 | | 4u-2/5=-4/5u-4/3 | | 5(1/2*y-3)-y=9 | | 3.5x+1.2=3.7-2.5x+3.7 | | (9x+8)(9x+3)= | | -1/2x-1/3=-4/5 | | (x-1)+2=2(x-3)+4x | | x=-5y^2 | | 3/2y-3=9 | | -1/3=6/5v-3/2 | | 5.7q-3.2-5.6q=-0.9q-5.1 | | 6+8x-4=2x+5-3 | | 4x+3y=380 | | 2x-1+x=4x-3 |